1994
DOI: 10.1111/j.1432-2277.1994.tb01335.x
|View full text |Cite
|
Sign up to set email alerts
|

Recipient hepatectomy with preservation of inferior vena cava reduces the need for veno-venous bypass in liver transplantation

Abstract: Recipient hepatectomy with inferior vena cava (IVC) preservation, the piggy back (PGB) technique, was adopted as our routine option in the management of the anhepatic phase of orthotopic liver transplantation (OLT) to avoid the use of veno-venous bypass (VV-BP). In the last 5 years, 119 OLT in adult patients have been performed in our unit. In the first period (47 OLT), VV-BP was used in 59% of the cases and cross-clamping in the rest. In the second period, following the introduction of the PGB technique, 72 O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 3 publications
0
18
0
1
Order By: Relevance
“…Different studies in CLTx have shown that the main proposed indications for using VVB are hemodynamic instability following test clamping of the IVC, impaired cardiac and renal function, fulminant hepatic failure (FHF), severe portal, massive bleeding during hepatectomy due to severe portal hypertension, and in cases with familial amyloidotic polyneuropathy during hepatectomy 15 27 31–37 . Proposed indications and their presumed pros and cons for the use of VVB are summarized in Table I, and claimed advantages and disadvantages of its use by different authors in Table II 15 27 31–37 .…”
Section: Venovenous Bypass In Cltxmentioning
confidence: 99%
“…Different studies in CLTx have shown that the main proposed indications for using VVB are hemodynamic instability following test clamping of the IVC, impaired cardiac and renal function, fulminant hepatic failure (FHF), severe portal, massive bleeding during hepatectomy due to severe portal hypertension, and in cases with familial amyloidotic polyneuropathy during hepatectomy 15 27 31–37 . Proposed indications and their presumed pros and cons for the use of VVB are summarized in Table I, and claimed advantages and disadvantages of its use by different authors in Table II 15 27 31–37 .…”
Section: Venovenous Bypass In Cltxmentioning
confidence: 99%
“…8 Recipient hepatectomy with preservation of the inferior vena cava and graft implantation with anastomosis of the donor suprahepatic inferior vena cava to a common channel of the three recipient hepatic veins was performed in both cases. Portal vein and hepatic artery anastomoses were performed before graft revascularization.…”
Section: Case Reportsmentioning
confidence: 99%
“…For the venous anastomosis the classical piggyback technique was used in all split‐liver transplantations (13), and the Belghiti technique with side‐to‐side cavo‐caval anastomosis in full organ transplantations (14). An extracorporal veno‐venous bypass was not necessary in any of the 34 transplantations.…”
Section: Methodsmentioning
confidence: 99%